Unrealistic models and how to identify them: on accounts of model realisticness - Claudius Gräbner (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2019)
What determines the realisticness of a model? It is argued that to come up with an account of model realisticness that can answer this question, one has to make strong philosophical commitments to an account of representation, an account of model-world comparisons as well as the ontology of models and their targets. Without such commitments it is not feasible to determine the realisticness of a model. Since all these areas are subject to ongoing philosophical debate, it is not feasible to come up with a unique and all-encompassing account. Based on this observation, one account of model realisticness, which is based on an antirealist fictional view of models, a commitment to realism about mathematical objects, and the DEKI account of representation, is introduced and discussed. The account aligns well with the practice of applied scientists, who regularly apply validation techniques to assess the realisticness of models. This practice can nicely be accommodated for in the proposed account, and it suggests a number of promising avenues for further philosophical inquiry.
Keywords: 330; Models; epistemology; fictionalism; representation; model-world comparisons